2018
DOI: 10.4236/jbm.2018.610005
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology for <i>Mycoplasma pneumoniae</i> Infection Using (Nursery) School Absenteeism Surveillance System, and Proposal for Countermeasures

Abstract: Objective: We present descriptive epidemiology of Mycoplasma infection using the (Nursery) School Absenteeism Surveillance System ((N)SASSy) in addition to national official sentinel surveillance for infectious diseases (NOSSID). It is expected to be helpful for early detection and response to outbreak of Mycoplasma infection and also to be useful for antimicrobial resistance measures. Method: The study period was 2010-2014 seasons. The study area was the whole of Ibaraki prefecture, Japan. NOSSID reports the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…These abnormalities may indicate that pneumonia is beneficial to the damage of the vascular mucosal endothelial layer and the exposure of thrombus collagen under the endothelium, which directly activates the platelets and prothrombin oxidase in the lungs of the children and leads to a hypercoagulable state. The results of clinical studies such as Lin Chunwang [ 24 ] showed that there is a hypercoagulable state in the lungs of children with severe pneumonia and causes the formation of acute microthrombosis in the lungs, D-deoxydimer (D-Dimor, dd) increased significantly, and the activity of AT-III decreased significantly. The activation time of thrombin kinase (TT) and the activation time of thrombin prokinase (APTT) in some children were significantly shorter than those in the normal infection control group, and the intra-arterial thrombin oxidase saturation (SaO 2 ) was significantly reduced.…”
Section: Experiments and Designmentioning
confidence: 99%
“…These abnormalities may indicate that pneumonia is beneficial to the damage of the vascular mucosal endothelial layer and the exposure of thrombus collagen under the endothelium, which directly activates the platelets and prothrombin oxidase in the lungs of the children and leads to a hypercoagulable state. The results of clinical studies such as Lin Chunwang [ 24 ] showed that there is a hypercoagulable state in the lungs of children with severe pneumonia and causes the formation of acute microthrombosis in the lungs, D-deoxydimer (D-Dimor, dd) increased significantly, and the activity of AT-III decreased significantly. The activation time of thrombin kinase (TT) and the activation time of thrombin prokinase (APTT) in some children were significantly shorter than those in the normal infection control group, and the intra-arterial thrombin oxidase saturation (SaO 2 ) was significantly reduced.…”
Section: Experiments and Designmentioning
confidence: 99%
“…We used information from (N)SASSy, which is useful for teachers and the persons concerned, such as officers at public health centers and local governments, to prevent the spread of infectious diseases [14][15][16]. Demonstrably, (N)SASSy is useful as a form of syndromic surveillance in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Nursery School Absenteeism Surveillance System ((N)SASSy) has been monitoring the health situation, diagnosed diseases or symptoms, of more than five million students or nursery school kids every day. It is a computerized system comprising a network of information shared among concerned organizations and individuals [10][11][12]. We can therefore use (N)SASSy as a form of syndromic surveillance in Japan.…”
Section: Discussionmentioning
confidence: 99%